2021
DOI: 10.1007/jhep10(2021)115
|View full text |Cite
|
Sign up to set email alerts
|

Bosonic η-deformed AdS4 × $$ \mathbb{CP} $$3 background

Abstract: We build the bosonic η-deformed AdS4 × $$ \mathbbm{CP} $$ CP 3 background generated by an r-matrix that satisfies the modified classical Yang-Baxter equation. In a special limit we find that it is the gravity dual of the noncommutative ABJM theory.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…In this paper we have obtained the bosonic η-deformed W 2,4 × T 1,1 and AdS 5 × T 1,1 backgrounds based on a solution of the mCYBE. These results provide new integrable backgrounds in addition to those found in [14,20,22]. In another context, Arutyunov et al [25] showed that it is possible to obtain an integrable T 1,1 background, which has an NSNS B-field.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…In this paper we have obtained the bosonic η-deformed W 2,4 × T 1,1 and AdS 5 × T 1,1 backgrounds based on a solution of the mCYBE. These results provide new integrable backgrounds in addition to those found in [14,20,22]. In another context, Arutyunov et al [25] showed that it is possible to obtain an integrable T 1,1 background, which has an NSNS B-field.…”
Section: Discussionmentioning
confidence: 68%
“…The extension of this construction, which is based on a solution of the modified classical Yang-Baxter equation (mCYBE), to a symmetric coset space was given by Delduc et al in [9], and to a semisymmetric coset space, as is the case of strings in AdS 5 × S 5 , in [10,11] 1 , leading to the so-called η-deformed AdS 5 × S 5 background in [12,13]. Recently, the σ-model on the supercoset uosp (2,2|6) so(1,3)⊕u (3) , which describes partially strings in AdS 4 × CP 3 , was considered in [14]. On the other hand, some instances of integrable deformations of the AdS 5 × S 5 and AdS 4 × CP 3 backgrounds were given based on solutions of the classical Yang-Baxter equation (CYBE) in [15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…This construction, which is based on a solution of the modified classical Yang-Baxter equation (mCYBE), can be extended to symmetric coset spaces [8] and to semi-symmetric coset spaces, as is the case of superstrings in AdS 5 × S 5 [9,10] leading to the so called η-deformed AdS 5 × S 5 background [11,12]. Recently, this kind of deformation was applied to the sigma model on the supercoset uosp (2,2|6) so(1,3)⊕u(3) which partially describes superstrings in AdS 4 ×CP 3 [13]. Besides that, some instances of integrable deformations of the AdS 5 × S 5 and AdS 4 × CP 3 backgrounds were also given based on solutions of the classical Yang-Baxter equation (CYBE) in [14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%